The Effect of Expressive Writing on the Health Conditions of College Students Amidst the COVID-19 Pandemic - Portia R. Marasigan (International Review of Social Sciences Research, 2022)
Expressive writing alludes to composing in which a person depicts profound considerations and sentiments encompassing the important event, the topic, or the area. As the world suffers from the COVID-19 pandemic, school and universities changed their teaching modalities from face-to-face teaching-learning process to online classes. Students were affected especially from lower socioeconomic localities of their limited financial ability to acquire the necessary equipment for learning and internet connection. In addition, they felt social isolation, lack of interaction with fellow students and the uncertainty of when the pandemic will be over. Hence, the study aimed to determine the effect of expressive writing on the psychological and physical conditions of the college students. The study used experimental design with pre-test and post-test and randomly assigned the respondents into the control group writing about their daily activities and the experimental group using expressive writing with each group has 60 respondents. The results showed that there is a significant difference in the health conditions between the experimental group treated with expressive writing and the control group treated with neutral condition. In conclusion, using expressive writing can overcome traumas and emotional upheavals thus resolves issues and improves health conditions.